Peptidic Ligands to Control the Three‐Dimensional Self‐Assembly of Quantum Rods in Aqueous Media. Issue 18 (26th May 2014) - Bizien, Thomas; Even‐Hernandez, Pascale; Postic, Marie; Mazari, Elsa; Chevance, Soizic; Bondon, Arnaud; Hamon, Cyrille; Troadec, David; Largeau, Ludovic; Dupuis, Christophe; Gosse, Charlie; Artzner, Franck; et al.
<x xml:space="preserve">Abstract</x> The use of peptidic ligands is validated as a generic chemical platform allowing one to finely control the organization in solid phase of semiconductor nanorods originally dispersed in an aqueous media. An original method to generate, on a macroscopic scale and with the desired geometry, three‐dimensional supracrystals composed of quantum rods is introduced. In a first step, nanorods are transferred in an aqueous phase thanks to the substitution of the original capping layer by peptidic ligands. Infrared and nuclear magnetic resonance spectroscopy data prove that the exchange is complete; fluorescence spectroscopy demonstrates that the emitter optical properties are not significantly altered; electrophoresis and dynamic light scattering experiments assess the good colloidal stability of the resulting aqueous suspension. In a second step, water evaporation in a microstructured environment yields superstructures with a chosen geometry and in which nanorods obey a smectic B arrangement, as shown by electron microscopy. Incidentally, bulk drying in a capillary tube generates a similar local order, as evidenced by small angle X‐ray scattering.